Storing Keitt Mangoes Using Eco-Friendly Treatments - Magdi Ismaiel Saif; Samar Imbaby; Mohamed S. M. Ali (Horticulturae)
The recent global trend aims to limit the use of chemicals in all aspects of our lives, necessitating research into the use of plant extracts and ultraviolet light as eco-friendly treatments to improve mango fruit storage. The literature did not introduce studies on plant extracts as coating materials for mango fruit storage. Although ginger, lemon, and green tea were utilized individually as edible coatings for some fruits, their combination in a single solution is not evaluated on mango fruits. To preserve the quality of Keitt mango fruit against decay during storage, fruits were treated with plant extracts (a mixture of ginger, lemon, and green tea), 50 g L−1 for each of them, and ultraviolet (UV) light, 250 nm for 5 min, either alone or in combination then stored at 22 °C or 13 °C. Data showed that the mixture of plant extracts treatment followed by the combination of plant extracts and UV treatment then UV treatments resulted in a decrease in weight loss and soluble solid contents (SSCs) compared to the control while reducing the decrease in firmness, acidity, vitamin C (Vit C), and phenols compared to the control. Mangoes stored at 22 °C reached 4 weeks with good quality while achieving 8 weeks at 13 °C.